Keterampilan Menulis Teks Deskripsi Berbasis Lingkungan Sekolah Siswa Kelas VII SMP Negeri 26 Makassar - Idamansari, Indah; Hamsa, Akmal; Idawati, Idawati (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
This study describes the skills of seventh-grade students at SMP Negeri 26 Makassar in writing descriptive texts based on the school environment using quantitative research. The research variable is a single variable, namely descriptive text writing skills. The research design used is a quantitative descriptive design, because the data and analysis are based on numbers. The population in this study was all seventh-grade students at SMP Negeri 26 Makassar in the 2024/2025 academic year, totaling 185 students, so the sample used was 26 students. The results of this study were measured using a student test instrument in writing descriptive texts based on the school environment, which were then analyzed using descriptive statistical methods and divided into three forms: frequency, average, and category. The results showed that the average student writing skill was 57.28. This score is still below the Minimum Competency (KKM) (70), so students' writing skills are categorized as insufficient.